Toposequent effect on morphology and classification of Ultisols soil in the Ayer Hitam Forest Reserve, Peninsular Malaysia - Aditya, Haidar Fari; Gandaseca, Seca; Rayes, Mochtar Lutfi; Karam, Daljit Singh (Department of Forestry, Faculty of Agriculture, University of Lampung, 2021)
Morphology in forest soils has developed over a long time due to the non-intensive management of forest soils. Damage to forest soil occurs when there is logging activity, fire, or land use change. Some forest was used as productive land for example agroforestry and forest production. As with landuse in agriculture, intensive management of forests can also reduce soil productivity. Inaccuracy forest land use would cause environmental or economic damage, so basic soil management data in forest areas is needed. However, the soil morphology of the Ayer Hitam Forest Reserve (AHFR) in Malaysiahas never been observed. The objective of this study is to assess the soil characteristic and soil morphological properties of the AHFR. Studying the characteristics of soil morphology in toposequent conditions is necessary to find out the differences in soil from different heights and the effects of erosion, transportation, and deposition on the soil. This study was conducted in the AHFR, Puchong, Selangor Darul Ehsan, Peninsular Malaysia. Mapping of the area under investigation was carried out by conventional soil survey techniques with a physiographic approach using maps with a scale of 1:30,000. The results showed that AHFR has some different soil morphological characteristics and classification in subgroupamong five different slope positions with similar soil order, which is a Ultisol soil. The soil in the AHFRis formed from highly weathered soil due to high rainfall in this location. The results of this study are important for soil development, identification management, and land use priority such as erosion control on steep-slope forest areas, regeneration and reforestation, and it can also be used for forest education, practice, research, and training activities.